{Comparison of salivary cortisol levels between women with functional hypothalamic amenorrhea and healthy women: a pilot study.} - Koukoubanis, Konstantinos; Stefanaki, Katerina; Karagiannakis, Dimitrios S; Kalampalikis, Andreas; Michala, Lina (Endocrine, 2023)
INTRODUCTION: Functional Hypothalamic Amenorrhea (FHA) has been associated with excessive-chronic stress, eating disorders, and weight loss. A common feature is the increased serum cortisol, but its measurement has many limitations. Currently, salivary cortisol (SC) has been proposed as a more sensitive and adequate index. AIM: To investigate the SC alterations through a 24-h period and the possible correlation with the severity of stress in women with FHA. METHODS: Between July 2019 and March 2021, 12 FHA women and 12 healthy controls of comparable age were included. Psychological, eating, and physical abnormalities were evaluated by applying equivalent validated self-questionnaires. RESULTS: No significant differences were found between FHA women and healthy individuals with respect to morning (8:00 am) serum cortisol and ACTH (522.5 ± 162.2 vs 442 ± 138.5 nmol/l; p = 0.204 and 37 ± 44.8 vs 17.4 ± 10.8 pg/ml; p = 0.186, respectively). Women with FHA had statistically significant higher morning SC compared to control subjects (21.8 ± 5.9 nmol/l vs 12.8 ± 3.8 nmol/l; p {<} 0.001), while no significant differences were found regarding the afternoon (4:00 pm) and midnight (12:00 am) SC. A significant positive correlation was found between morning SC and morning serum cortisol (rho = 0.532; p = 0.007), EAT-26 (rho = 0.527; p = 0.008) and HADS-Anxiety score (rho = 0.471; p = 0.02). Additionally, a significant negative correlation between morning SC and BMI was observed (rho = -0.53; p = 0.009). CONCLUSION: Compared to serum cortisol, SC seems to express better the hypercortisolemic state of women with FHA and correlates well with the underlying contributing factors. Larger studies are needed in order to confirm these results and validate the optimal SC cut-off value associated with the development of FHA.
Keywords: Amenorrhea; Female; Humans; Hydrocortisone; Hypothalamic Diseases; Luteinizing Hormone; Pilot Projects